Existence of positive solutions for a system of fourth-order differential equations - Hailong Ma; Hongyu Li (Journal of Inequalities and Applications)
Abstract In this paper, we study a system of fourth-order differential equations with integral boundary conditions and two parameters. By using the Guo–Krasnoselskii fixed point theorem on a cone and some properties of Green’s function we obtain the existence of positive solutions for the system of fourth-order differential equations and provide two examples to verify our main results.